2015
DOI: 10.3389/fpsyg.2015.01143
|View full text |Cite
|
Sign up to set email alerts
|

Occupational coping self-efficacy explains distress and well-being in nurses beyond psychosocial job characteristics

Abstract: Aim: The main purpose of the present study was to extend the Job Demand Control Support (JDCS) model analyzing the direct and interactive role of occupational coping self-efficacy (OCSE) beliefs.Background: OCSE refers to an individual’s beliefs about their ability to cope with occupational stressors. The interplay between occupational stressors, job resources, and self-efficacy beliefs is poorly investigated. The present research attempts to address this gap.Design: Cross-sectional survey.Method: Questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 80 publications
3
56
0
3
Order By: Relevance
“…Notably, the Italian participant characteristics were similar to those of a study with a 12‐fold larger cohort of nurses from other Italian hospitals (Pisanti et al. ), while the Korean nurse characteristics were similar with those of a previous survey on nurse activities (Korea Health Industry Development Institute ). Therefore, our participants, at least with regard to demographic and personal characteristics, were not dissimilar from other populations of Italian and Korean hospital nurses.…”
Section: Discussionsupporting
confidence: 77%
“…Notably, the Italian participant characteristics were similar to those of a study with a 12‐fold larger cohort of nurses from other Italian hospitals (Pisanti et al. ), while the Korean nurse characteristics were similar with those of a previous survey on nurse activities (Korea Health Industry Development Institute ). Therefore, our participants, at least with regard to demographic and personal characteristics, were not dissimilar from other populations of Italian and Korean hospital nurses.…”
Section: Discussionsupporting
confidence: 77%
“…Nursing work is demanding and stressful, which is often associated with poor well-being (e.g., Sorgaard et al, 2010; Pisanti et al, 2011, 2015; Purcell et al, 2011; Giorgi et al, 2016). Most nurses are women (in Poland, 96%) who traditionally must reconcile professional demands with responsibilities for the family.…”
Section: Introductionmentioning
confidence: 99%
“…Intervention programmes designed to develop positive psychological resources could also be implemented. For example, Pisanti et al (2015) reported that nursing staff with higher levels of occupational coping self-efficacy experienced higher levels of well-being. Evidence exist that such state-like positive psychological resources, like self-efficacy, can be developed through training initiatives It is also recommended that organisations develop tailored selection procedures that incorporate consideration of certain personal resources, such as a sense of calling.…”
Section: Managerial Implicationsmentioning
confidence: 99%